Developing the textbook "Arabic Language Lessons in the Modern Way" In The Illustrated Dictionary To Upgrade Students' Reading Skills (Research Development At The Insan Qurani Institute Aceh Besar): (Aceh Besar البحث والتطوير بمعهد إنسان قرآني) تطوير الكتاب المدرسي "دروس اللغة العربية على الطريقة الحديثة" بالقاموس المصور لترقية قدرة الطلاب على مهارة القراءة - Syahda, Zakkia; Badruzzaman, Badruzzaman (EL-MAQALAH : Journal of Arabic Language Teaching and Linguistics, 2024)
In this research, the researcher developed the textbook “Durus Al-Lughah Al-‘Arabiyyah ‘Ala Ath-Thariqah Al-Haditsah” With The Picture Dictionary To Improve Students’ Ability In Reading Skills (Research And Development At Insan Qur’ani’s Islamic Boarding School, Aceh Besar). The researcher conducted the observation in the 7th grade at Insan Qur’ani’s Islamic Boarding School, Aceh Besar. The problem that students face when learning the Arabic language is their weak understanding of the studied material due to their lack of control over new Arabic vocabulary and words. The objectives of this research are: 1) To know the procedure for developing the textbook “Durus Al-Lughah Al-‘Arabiyyah ‘Ala Ath-Thariqah Al-Haditsah” with the picture dictionary in improving students’ ability in reading skills. 2) To determine the validity of the picture dictionary in improving students’ ability in reading skills. 3) To know the effectiveness of the picture dictionary in improving students’ ability in reading skills. The research method used is Research & Development. The picture dictionary development process uses the ADDIE development model, with five stages, namely analysis, design, development, implementation, and evaluation. The results of the research are: 1) The process of developing the picture dictionary is used to teach reading skills using the ADDIE development model with five stages, namely analysis, design, development, implementation, and evaluation. 2) Based on the Picture Dictionary's eligibility guidelines, the Picture Dictionary's criteria is "Excellent", with details of the design expert's validation results, and the criteria received a "Very Good" score of 80%. The content expert's validation results receive an "excellent" criteria of 85%. The results of the picture dictionary answer questionnaire from students obtained criteria of “excellent” with a value of 91.14%. 3) The effectiveness of using the picture dictionary was proven by increasing the average score of the students’ learning outcomes test. It is known that the average score of the pre-test for the experimental class was 64.05 and the average score of the post-test was 87.14. While in the control group, the average score of the pre-test was 52.62 and the average score of the post-test was 74.29. Therefore, it can be concluded that there is an increase in learning results using the picture dictionary in teaching reading skills in the 7th grade at the Insan Qur’ani’s Islamic Boarding School, Aceh Besar.